Ternary FePSe3 Atomic Layers with Competitive Temperature Coefficient of Resistance for Uncooled Infrared Bolometers. Issue 18 (23rd August 2021) - Li, Alei; Ge, Yanfeng; Gan, Yuan; Ren, Yulu L.; He, Yingjie; Chen, Qianxue; Wang, Peipei; Zhang, Kai; Yang, Shengyuan A.; Wu, Judy Z.; Chen, Rui; Zhang, Liyuan; et al.
Abstract: The semiconducting metal phosphorus trichalcogenides (MPX3, X = S, Se), a new family of layered atomic materials similar to the transition‐metal dichalcogenides, have recently attracted great attention owing to their 2D magnetic properties as well as their wide range of tunable bandgaps, which can lead to promising applications in spintronic and optoelectronic devices. Herein, an uncooled bolometer based on FePSe3 atomic layers is reported, on which a competitive temperature coefficient of resistance (TCR) of ≈−2.96% K −1 at room temperature is observed. In detecting infrared radiation (980–1550 nm) at room temperature using the FePSe3 bolometer, high responsivity exceeding 10 8 V W −1 and specific detectivity up to 10 9 Jones are achieved, which can be attributed to the combined advantages of the competitive room‐temperature TCR and natural thermal isolation between the inner layers of FePSe3 and the environment. This result reveals a remarkable property of FePSe3 atomic layers and paves the way toward new types of bolometers with high sensitivities. Abstract : FePSe3 atomic layers bolometers present an excellent thermal infrared radiation detection with responsivity and specific detectivity exceeding ≈1 × 10 8 V W −1 and ≈1 × 10 9 Jones under 1550 nm short‐wave infrared illumination at room temperature, which is on par with the current state‐of‐the‐art conventional bolometers that require suspended structure for thermal isolation and hence improved signal‐to‐noise ratios.